Ekosistem Pertanian Untuk Mendukung Regenerasi Petani Indonesia - Widjanarko, Nadila Puspa Arum; Subejo, Subejo; Raya, Alia Bihrajihant; Wirakusuma, Gilang; Untari, Dyah Woro; Sari, Almonika Cindy Fatika; Sugiyarto, Sugiyarto; Ansari, Andrianto; Akhda, Najmu Tsaqib; Muttaqin, Andi Syahid; Permana, Rusdi Al Rosid Ilham; Fatonah, Siti (AGRITEXTS: Journal of Agricultural Extension, 2026)
A notable trend in Indonesia's agricultural sector is the aging of its farmer population. The reluctance of the younger generation to pursue careers in the agricultural sector is attributed to pervasive negative perceptions, including the lacks societal prestige. In an effort to increase farmer succession, the Ministry of Agriculture, in collaboration with IFAD, has initiated the YESS. This program offers internships, training, funding through competitive grants, and the development of young agricultural entrepreneurs for young generations. The objective of this study is to analyze the impact of the YESS on the agricultural ecosystem and to identify the agricultural ecosystem with the most influence in supporting farmer succession. The present study involved 120 beneficiaries of the YESS in West Java, East Java, South Kalimantan, and South Sulawesi selected through purposive sampling. The analysis was conducted using multidimensional scaling, agricultural human resources and agricultural regulations. The findings of the present study indicate that the regulatory framework governing agriculture the proliferation of farmer succession in Indonesia. The extent to which existing agricultural regulations are implementable and representative is directly correlated with the number of farmer successions. Achieving this objective necessitates a collaborative effort among the Ministry of Agriculture, in its capacity as the policy maker, academics, young farmers, young agricultural entrepreneurs, and relevant stakeholders to achieve sustainable farmer succession.